TENOR CONFIGURATIONS IN CAMPAIGN SPEECHES OF TWO DEMOCRATIC PARTY PRESIDENTIAL CANDIDATES 2016 - Yeni Novita Sari and Syamsul Bahri (LINGUISTICA, 2017)
This study aims at finding out the tenor configurations that exist in the campaign speeches of two Democratic Party presidential candidates 2016 by using four aspects of tenor and it is to find out how the way the social relationship is played by addressee and addresser in political arena. Tenor configurations in campaign speeches of two Democratic Party presidential candidates is done by theory of Systemic Functional Linguistics. The use of tenor is purposed to make readers understand the speech easily and persuade the readers to do something as the speech means. This research used descriptive quantitative method. The data of this study were taken from some sources in the internet. The data were the transcripts of four campaign speeches by two Democratic presidential candidates that were delivered in different places. The writer focused on the analysis of aspects of tenor in campaign speeches by two Democratic Party presidential candidates; Hillary Clinton and Bernie Sanders, and finally found the most dominant configuration that appears in the campaign speeches. The writer found that from the four aspects of tenor the campaign speeches mostly used configuration [Formal/Equal/Positive/Infrequent].